Biochemical characteristics of cellulose and a green alga degradation by Gilvimarinus japonicas 12-2T, and its application potential for seaweed saccharification. Issue 12 (2nd December 2018) - Kouzuma, Shousei; Fujii, Katsuhiko
ABSTRACT: Cellulose is one of the major constituents of seaweeds, but reports of mechanisms in microbial seaweed degradation in marine environment are limited, in contrast to the multitude of reports for lignocellulose degradation in terrestrial environment. We studied the biochemical characteristics for marine cellulolytic bacterium Gilvimarinus japonicas 12-2 T in seaweed degradation. The bacterial strain was found to degrade green and red algae, but not brown algae. It was shown that the bacterial strain employs various polysaccharide hydrolases (endocellulase, agarase, carrageenanase, xylanase, and laminarinase) to degrade seaweed polysaccharides. Electrophoretic analysis and peptide sequencing showed that the major protein bands on the electrophoresis gel were homologous to known glucanases and glycoside hydrolases. A seaweed hydrolysate harvested from the bacterial culture was found useful as a substrate for yeasts to produce ethanol. These findings will provide insights into possible seaweed decomposition mechanisms of Gilvimarinus, and its biotechnological potential for ethanol production from inedible seaweeds. Graphical abstract: : Putative mechanism for seaweed decomposition by Gilvimarinus japonicas 12-2 T .